Empowering Educators, Supporting Students: A Quasi-Experimental Evaluation of a Train-the-Trainer Model for School Mental Health in Indonesia - Ahmad Badruddin; Omar Alieva; Ifah Shandy; Henny Kesuma; Benyamin Wongso; Winata Putri; Habiburrahman Said (Indonesian Community Empowerment Journal, 2025)
Adolescent mental health is a pressing concern in urban Indonesian schools, where a significant gap exists between student needs and the availability of professional support. This study evaluated the efficacy of a culturally-adapted, school-based "Train-the-Trainer" (TtT) community service model designed to build sustainable mental health support capacity by empowering teachers. A quasi-experimental study with a matched control group was conducted in 20 public high schools in South Sumatera, Indonesia. Ten schools (n=150 teachers, n=1500 students) received the TtT intervention, where core teachers were trained to cascade mental health literacy and foundational support skills to their peers. Ten matched schools (n=145 teachers, n=1450 students) served as a control group. Data on teacher self-efficacy, student-reported support awareness, and school mental health policies were collected at baseline, 6-months, and 12-months. A linear mixed-effects model revealed a significant time-by-group interaction, with teachers in the intervention group reporting substantially higher confidence in supporting students at 12 months (M=4.15, 95% CI [4.01, 4.29]) compared to the control group (M=2.51, 95% CI [2.37, 2.65]), a large effect (d=2.41). Intervention students were significantly more likely to know how to access support (78% vs. 27%; OR=9.82, 95% CI [8.11, 11.89], p < 0.001). Intervention schools demonstrated a massive increase in formalized mental health protocols compared to control schools (IRR=7.94, p < 0.001). In conclusion, the TtT model is a highly effective and scalable strategy for building a foundational mental health support system within existing school structures in resource-constrained settings. By investing in local educators, this model fosters a sustainable, multi-tiered support ecosystem, offering a viable pathway for national policy and practice in Indonesia.